PERAN GURU DALAM MEMBERI PERLINDUNGAN TERHADAP ANAK (PERSEFEKTIF KEBIJAKAN HUKUM NARKOBA) - Rizqiyana Rizqiyana; Muhammad Ghozali (MEDIOVA: Journal of Islamic Media Studies, 2023)
This paper aims to describe the role of teachers in providing protection to children from the point of view of drug law policy by formulating the problem of how the protection is by teachers children who abuse drugs. This study uses a qualitative research methodology. This type of research is under the umbrella of library research, namely research conducted through library research. The findings of this study are used to guide efforts to transfer children from the formal criminal justice system to non-formal criminal justice systems in order to keep them from becoming addicted to drugs. One of the distinctive aspects of this diversion technique is the participation of multiple stakeholders. Diversion differs from mediation in that it involves more than just the parties to the conflict; that mediation only involves conflicting parties, diversion also involves other parties such as community leaders, parents (children of perpetrators), religious leaders, law enforcement officers, and teachers. But among all those involved, the instructor was the one who had a significant impact. Because teachers function as surrogate parents, have more time with children than other adults, and help shape children's personalities.